Symptom Resolution and Recurrence Outcomes after Partial Versus Total Laparoscopic Adrenalectomy: 13 years of Experience with Medium-Long Term Follow up: Partial vs. Total adrenalectomy - Simforoosh, Nasser; Soltani, Mohammad Hossein; Shemshaki, Hamidreza; Bonakdar Hashemi, Milad; Dadpour, Mehdi; Kashi , Amir H (Urology Journal, 2020)
Purpose: Partial adrenalectomy (PA) is an emerging modality typically performed for the treatment of hereditary and sporadic bilateral tumors, to reduce the risk of adrenal failure. In this study, we evaluated the recurrence and functional outcomes after partial and total adrenalectomy (TA). Materials and methods: From March 2005 to July 2018, 284 patients with functional tumor or > 5 cm adrenal mass underwent clipless and sutureless laparoscopic partial or total adrenalectomy (PLA and TLA). Patients with a pathological diagnosis of pheochromocytoma, Cushing or Conn’s disease and more than two year follow up were included in this study. Pre-operative and operative variables were collected retrospectively and functional outcomes and recurrence were gathered prospectively. Results: One hundred forty patients (mean age: 43±5.1years) were included in the study. PLA and TLA were performed for pheochromocytoma (total n=78; PLA=12 (15%), TLA=66 (85%)), Cushing syndrome (toal n=17; PLA = 4 (24%), TLA = 13 (76%)), and Conn’s disease (total n=45; PLA=7 (16%), TLA=38 (84%)). In pheochromocytoma patients, improvement of hypertension, palpitation, and headache was not different between patients who underwent PLA versus TLA (all P > 0.05). Two recurrences were observed in patients with pheochromocytoma who had undergone TLA. In patients with Cushing disease, central obesity, fascial plethora, and hypertension were improved in all patients six months after treatment, muscle weakness was improved one year after surgery, and acne and hyperpigmentation only improved two years after surgery. The length of time for resolution of symptoms was not different in patients who underwent PLA versus TLA. In Conn’s disease hypertension was resolved in all patients and no patient required potassium supplements post-operatively. In follow up no recurrence was observed in patients with a pathological diagnosis of Cushing or Conn’s disease. Conclusion: In our experience, PLA can provide excellent control of the symptoms parallel with TLA and with no statistically significant difference in recurrence making PLA an attractive option in patients with an adrenal mass.